Narrative Framing of the Syrian Refugee Crisis in British Religious News - Perreault, Gregory (Journal of religion, media and digital culture, 2019)
This paper examines how religious news organizations in the UK covered the Syrian refugee crisis in Europe. Using narrative framing theory, this paper examines all coverage from 2015 and 2016 published in bbc Religion (a part of bbc News), The Muslim News, and Christian Today to examine shared and disparate narratives regarding Syrian refugees migrating to the UK. Four major frames emerged from our analysis of the media coverage in religious and mainstream publications: a humanizing frame, saviour frame, dehumanizing frame, and, redemption frame. The publications differed in their use of these frames as well as the use of sources, news values, and tone of coverage. We discuss each of these frames as well as the implications of the differing coverage.